The trend of feminization of doctors' workforce in Oman: is it a phenomenon that could rouse the health system? - Nazar A. Mohamed; Nadia Noor Abdulhadi; Abdullah A. Al-Maniri; Nahida R. Al-Lawati; Ahmed M. Al-Qasmi (BMC, 2018)
Abstract Background Participation of women in the medical profession over several countries worldwide was increased over the past decades. This paper is a part of ongoing studies aiming at addressing the issue of health workforce feminization among doctors in the Sultanate of Oman as well as exploring the health system readiness in dealing with this phenomenon. Methods Literature in addition to reports and records of the Ministry of Health, Oman (MoH), Sultan Qaboos University (SQU) and Oman Medical Specialty Board were reviewed regarding the gender of the doctors and the medical students. Results Findings regarding the medical students at the SQU showed higher number of females compared to males (64% females in 2015 compared to 54% in 2009). A similar trend was observed regarding the postgraduates as 61.5% of the graduated residents doctors were females. As for active workforce, the MoH 2015 report revealed that female doctors represent 42% of the total doctors compared to 27% in 1990. It increased 4% from 1990 to 2000, doubled to 8% from 2000 to 2010. The proportion of specialized female doctors reached 31% in 2015 compared to 21% in 1990. There were also gender variations among specialities. The proportion of female general practitioners reached 50% in 2015 compared to 30% in 1990 (4% increase every 5 years). Conclusions The feminization phenomenon in Oman is increasing and requires more attention in order to assess the health system readiness of meeting the needs and accommodating the females as the main care providers. The trend is expected to have important consequences on future planning, given that women doctors differ from men in how they participate in the workforce. It may also potentially contribute to a shortage in supply due to difference in preferences and consequently affect the skill-mix and productivity. The cultural, social context and dimensions need to be explored and feasible options to be provided for better planning.